2021
DOI: 10.1186/s12951-021-00775-x
|View full text |Cite
|
Sign up to set email alerts
|

Tailored liposomal nanotraps for the treatment of Streptococcal infections

Abstract: Background Streptococcal infections are associated with life-threatening pneumonia and sepsis. The rise in antibiotic resistance calls for novel approaches to treat bacterial diseases. Anti-virulence strategies promote a natural way of pathogen clearance by eliminating the advantage provided to bacteria by their virulence factors. In contrast to antibiotics, anti-virulence agents are less likely to exert selective evolutionary pressure, which is a prerequisite for the development of drug resist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…In our previous work, we established that bacterial culture supernatants obtained from both GAS and GGS strains were highly lytic towards erythrocytes [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous work, we established that bacterial culture supernatants obtained from both GAS and GGS strains were highly lytic towards erythrocytes [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, supernatants obtained from both GGS strains were more active against Raji cells than against THP-1 cells ( Figure 1 c,d). We have previously shown that GAS strains rely to a greater extent on SLO, whereas GGS preferentially use SLS for their hemolytic activities [ 21 ]. Therefore, our data suggest that SLO and SLS differ in their ability to harm different types of immortalized immune cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations